Beyond Traditional Methods: Unraveling The Influence Of Modern Nursing Education On Patient Satisfaction And Quality Care In KSA - A Systematic Review (Journal of Namibian Studies : History Politics Culture, 2022)
Background: The rationale for this research is the growing body of evidence supporting the critical relationship between nurse staffing levels of education and patient outcomes in healthcare settings. As evidence of the impact of staffing on patient safety, quality of care, and overall satisfaction mounts, it is necessary to comprehend the particular nuances within the Saudi Arabian healthcare context. This study aims to review the effectiveness of nursing education in improving patient satisfaction and quality of care in KSA.Method: A thorough search of databases, including Scopus, PubMed, and Web of Science, was conducted in order to categorize relevant research that was published between 2018 and 2022. The inclusion criteria for this research were English-language papers that focused on nursing education and patients’ satisfaction and quality of care perceived in the healthcare centers. The selected studies also have to offer useful information on team dynamics and employ recognized measurement scales. Following an initial screening and quality evaluation, eleven studies were included in the synthesis.Results: The study database was searched through electronic databases, identifying 11534 records. 20 unique records were assessed for eligibility based on titles and abstracts. After initial screening, 20 studies were selected for full-text assessment. After independent review, 11 studies met criteria and were included in the systematic review. The selected studies were conducted between 2018-2022 and varied in design. The PRISMA flowchart illustrates the selection process. Quality evaluation involves peer-reviewed journals, overall assessment, and quality management.Conclusion: It is concluded that systematic review of nursing education in Saudi Arabia reveals the need for comprehensive programs and supportive work environments to enhance patient satisfaction and care quality. It suggests prioritizing patient-centered care, leveraging digital health technologies, and promoting continuous quality improvement initiatives to elevate nursing care standards. These recommendations can enhance healthcare services and patient well-being in Saudi Arabia.